二语水平对汉语悲伤通感隐喻认知的影响研究 - Cheng Haiting (Sinolingua: Journal of Chinese Studies, 2024)
In this study, Chinese songs containing sadness metaphors were used as experimental materials to investigate the relationship between the level of bilingualism and the perception of Chinese sadness metaphors. Native Chinese speakers perceived sadness more highly in songs with lyrics, but Chinese bilinguals' perception of sadness was not affected by the presence or absence of lyrics. Highly proficient Chinese bilinguals perceived the Chinese sadness metaphor to a relatively higher degree. This study suggests that in Chinese language teaching, especially cultural teaching, teachers can use the sadness inducing effect of sad tunes on listeners to assist students from different cultural backgrounds to understand and remember and use relevant expressions with sadness emotion metaphors in Chinese.